2014
DOI: 10.2147/ijn.s72318
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mucosal immune responses and protection of cattle against direct-contact challenge by intranasal delivery with foot-and-mouth disease virus antigen mediated by nanoparticles

Abstract: The aim of this study was to enhance specific mucosal, systemic, and cell-mediated immunity and to induce earlier onset of protection against direct-contact challenge in cattle by intranasal delivery of a nanoparticle-based nasal vaccine against type A foot-and-mouth disease (FMD). In this study, two kinds of nanoparticle-based nasal vaccines against type A FMD were designed: (1) chitosan-coated poly(lactic-co-glycolic acid) (PLGA) loaded with plasmid DNA (Chi-PLGA-DNA) and (2) chitosan-trehalose and inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…A single study in cattle assessed two types of nanoparticle nasal vaccines against serotype A FMDV: i) chitosan‐coated polylactic‐co‐glycolic acid (PLGA) loaded with plasmid DNA encoding sections of P1, 2A and 3C; and ii) chitosan–trehalose loaded with inactivated FMDV. The DNA‐based vaccine was the more promising of the two, inducing specific IgA production in the nasal mucosa from 4 days post‐immunization and protecting three out of four animals from challenge (Pan et al., ). Continued investigation of needle‐free vaccination is needed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A single study in cattle assessed two types of nanoparticle nasal vaccines against serotype A FMDV: i) chitosan‐coated polylactic‐co‐glycolic acid (PLGA) loaded with plasmid DNA encoding sections of P1, 2A and 3C; and ii) chitosan–trehalose loaded with inactivated FMDV. The DNA‐based vaccine was the more promising of the two, inducing specific IgA production in the nasal mucosa from 4 days post‐immunization and protecting three out of four animals from challenge (Pan et al., ). Continued investigation of needle‐free vaccination is needed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Intranasal delivery of cationic PLGA nano/microparticles loaded with various FMDV DNA vaccine formulations encoding IL-6 as a molecular adjuvant enhanced protective immunity against infection by aerosolized FMDV [20]. Another study also suggested that intranasal delivery of Chi-PLGA-DNA nanoparticles with FMDV antigen resulted in high levels of mucosal, systemic and cell-mediated immunity and could reduce disease severity and virus excretion as well as delay clinical symptoms [23]. .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study that utilizes chitosan nanoparticles as carriers for an intranasal vaccine against fungi, although chitosan nanoparticles have already been used in intranasal vaccines against viral infections [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%